1986
DOI: 10.1007/bf00381379
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic low-level exposure to lead on plasma immunoglobulin concentration and cellular immune function in man

Abstract: The immunological status of individuals occupationally exposed to low levels of inorganic lead has been examined and compared with that of non-exposed, age and sex-matched controls. At the time of testing the exposed population had a mean (+/- SD) blood lead concentration of 38.4 +/- 5.6 micrograms X 100 ml-1 (n = 39) compared with a mean value of 11.8 +/- 2.2 micrograms X 100 ml-1 (n = 21) for the control group. No differences in the serum concentrations of IgG, IgA and IgM between the populations were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 14 publications
4
17
0
Order By: Relevance
“…Some previous studies in human subjects exposed to lead have failed to detect any changes in NK cell subpopulations or NK cell activity (Kimber et al 1986;Fischbein et al 1993b). It seemed to be difficult to control confounding factors such as exposure to other chemical compounds, smoking and ageing.…”
Section: Discussionmentioning
confidence: 97%
“…Some previous studies in human subjects exposed to lead have failed to detect any changes in NK cell subpopulations or NK cell activity (Kimber et al 1986;Fischbein et al 1993b). It seemed to be difficult to control confounding factors such as exposure to other chemical compounds, smoking and ageing.…”
Section: Discussionmentioning
confidence: 97%
“…Fifteen of the 51 firearm instructors had PbBs ≥25 μg/dL (mean 31.4 μg/dL), whereas the rest had a mean PbB of 14.6 μg/dL. In contrast, Kimber et al (1986) reported that responses to PHA and NK cell activity were not altered in their study of workers whose mean PbB was 34.8 μg/dL, compared with an unexposed group with a mean PbB of 11.8 μg/dL. Pinkerton et al (1998) found no alterations in lymphoproliferative responses to tetanus toxoid or in NK cell activity in workers with a median PbB of 39 μg/dL.…”
Section: Health Effectsmentioning
confidence: 90%
“…Workers exposed occupationally for 4-30 years, and whose PbB at the time of testing ranged from 25 to 53 μg/dL (mean, 38.4 μg/dL), had serum concentrations of IgG, IgA, and IgM not significantly different from unexposed controls whose PbB at the time of testing ranged from 8 to 17 μg/dL (mean, 11.8 μg/dL) (Kimber et al 1986). Alomran and Shleamoon (1988) (Basaran and Ündeger 2000;Ündeger et al 1996).…”
Section: Health Effectsmentioning
confidence: 92%
“…A study in rats after chronic lead exposure showed a significant depression in serum IgG levels (Luster et aL, 1978). However, reported levels appear to be unaffected by lead in rabbits (Gainer, 1974), children with 40 ~tg dL "1 PbB (Reigart and Graber, 1976), and adult lead workers (Ewers et aL, 1982;Kimber et al, 1986). Specific antibody levels (i.e., the response to a specific antigenic challenge) were reduced by lead in several animal studies (Blakely etal., 1980;Koller, 1973;Stankovic and Jugo, 1976;Koller and Roan, 1980;Rosenberg et al, 1985).…”
Section: Introductionmentioning
confidence: 91%